Informal allopathic provider knowledge and practice regarding control and prevention of TB in rural Bangladesh - Islam, Qazi S.; Ahmed, Syed M.; Islam, Mohammad A.; Chowdhury, Anita S.; Siddiquea, Bodrun N.; Husain, Mohammad A. (International Health, 2016)
Includes bibliographical references (page 231).